Airway-Clearance Techniques in Children and Adolescents with Chronic Suppurative Lung Disease and Bronchiectasis - Lee, Annemarie L.; Button, Brenda M.; Tannenbaum, Esta-Lee (Frontiers in Pediatrics, 2017)
Common symptoms of chronic suppurative lung disease or bronchiectasis in children and adolescents are chronic cough with sputum production, retention of excess secretions in dilated airways and a history of recurrent infections. Clinical management includes the prescription of airway clearance techniques to facilitate mucociliary clearance, optimize sputum expectoration, relieve symptoms and improve well-being. A wide range of airway clearance techniques are available for selection and these strategies may be applied in isolation or in combination. The choice of technique will depend in part on the age of the child, their clinical state and factors which may influence treatment adherence. While the evidence base for airway clearance techniques in children and adolescent with these conditions is not robust, the current available evidence in addition to clinical expertise provides guidance for technique prescription and clinical effect. An overview of the most commonly applied airway clearance techniques, including their physiological rationale and discussion of factors influencing prescription in children and adolescents is outlined in this review.